High-risk human papillomavirus-associated vulvar neoplasia among women living with human immunodeficiency virus in Zambia - Fred Maate; Peter Julius; Stepfanie Siyumbwa; Leeya Pinder; Trevor Kaile; Mulindi Mwanahamuntu; Groesbeck Parham (AOSIS, 2022)
Background: Globally, women living with HIV have a higher risk of vulvar neoplasia than HIV-negative women. Vulvar neoplasia among women living with HIV has not previously been characterised in Zambia. Objective: This study determined the clinical and pathologic features of vulvar neoplasia among women living with HIV at the University Teaching Hospital, Lusaka, Zambia. Methods: We conducted a cross-sectional study of vulvar lesions among 53 women living with HIV who presented with vulvar lesions between July 2017 and February 2018. The study assessed clinical and histological characteristics and prevalence of high-risk human papillomavirus (HRHPV). Results: Twenty-one patients were diagnosed with vulvar squamous cell carcinoma (VSCC), 20 with usual vulvar intraepithelial neoplasm (uVIN), and the rest with either benign lesions or non-neoplastic lesions (NNL). Participants' mean age was 40 years. Patients with VSCC were significantly older than those with NNL (mean (s.d.): 43 (21) vs 33 (10), p = 0.004). The prevalence of HRHPV was 88.9% in VSCC patients and 100.0% in high-grade squamous intraepithelial lesion patients. HPV16 was the most common (52.6%) genotype. The clinical features of neoplasia were similar to those of NNL. Conclusion: VSCC was significantly more common among women aged ≥ 40 years. HRHPV in VSCC and high-grade squamous intraepithelial lesions was high. Women with vulvar lesions, especially those aged 40 years, should be evaluated for vulvar cancer. Young girls should be vaccinated to prevent vulvar cancer.